73 DNACPR practice: has the tracey judgement made a difference?. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Freeman, Natasha; Clarke, Beverley; Macfarlane, Michael; Willis, Derek
Abstract : Background: A study earlier this year 1 suggested that the 2014 Court of Appeals decision (The Tracey Judgement) had led to Do Not Attempt Cardiopulmonary Resuscitation (DNACPR) decisions being discussed more frequently with patients and their families in the hospice setting but there was a lack of clarity on what physical or psychological harm these discussions could cause. We aimed to survey current practice amongst non-palliative care doctors and Clinical Nurse Specialists (CNS) regarding making and communicating DNACPR decisions, the impact of the Tracey judgement on their practice and their interpretations of harm. Method: An online anonymous survey was distributed to GPs, Consultants and CNSs in the West Midlands. Results: 89 responses were received (68% GPs, 24% consultants, 7% CNSs). 90% reported making DNACPR decisions on a regular basis. Reasons for not making DNACPR decisions included lack of time (50%), responsibility lying with others (26%) and fear of medicolegal consequences (13%). Barriers to communicating DNACPR decisions included mental capacity of the patient (76%), fear of causing distress (24%) and lack of time (21%). 51% of respondents were aware of the 2014 Tracey judgement and 24% reported it had changed their practice. Common themes regarding harm included a physical aspect (26%), harm to patients (23%), psychological distress (18%) and emotional impact (9%). Conclusions: These results suggest there are significant barriers to making and communicating DNACPR decisions and a lack of awareness about the Tracey judgement amongst non-palliative care doctors. Although some common themes emerged regarding interpretations of harm, the variation within this group suggests individual beliefs and values may influence interpretation of harm. Reference: . Macfarlane M, Shayler S, Nelms L, WM CARES Group, et al. Tracey judgement and hospice DNACPR orders: steady as she goes or seismic change?BMJ Supportive & Palliative Care 25 July 2018. doi:10.1136/bmjspcare-2018-001518